2022
DOI: 10.3389/fmed.2022.914356
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and irritable bowel syndrome: A systematic review and meta-analyses

Abstract: ObjectiveTo estimate the pooled odds ratio of endometriosis and irritable bowel syndrome, and to estimate the pooled prevalence of irritable bowel syndrome in patients with endometriosis.Data sourcesUsing Cochrane Library, MEDLINE, Science Direct, ClinicalTrials.gov, Web of Science, and CINAHL, we conducted a systematic literature search through October 2021, using the key terms “endometriosis” and “irritable bowel syndrome.” Articles had to be published in English or Spanish. No restriction on geographical lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
2
12
0
1
Order By: Relevance
“…In our sample, 38.5% ( n = 533) of respondents reported to have been diagnosed with IBS, with most (80%, n = 427) having been diagnosed prior to endometriosis. These values are slightly higher than those reported in the three aforementioned systematic reviews 11,12,30 ; however, our sample may have been biased because those with gut symptoms were more likely to participate and diagnoses of both conditions were self‐reported. Nevertheless, although global symptom relief, pain when opening bowels and stool type were all significantly worse in respondents with IBS, more than half of IWE without IBS also had abnormal findings for these parameters.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In our sample, 38.5% ( n = 533) of respondents reported to have been diagnosed with IBS, with most (80%, n = 427) having been diagnosed prior to endometriosis. These values are slightly higher than those reported in the three aforementioned systematic reviews 11,12,30 ; however, our sample may have been biased because those with gut symptoms were more likely to participate and diagnoses of both conditions were self‐reported. Nevertheless, although global symptom relief, pain when opening bowels and stool type were all significantly worse in respondents with IBS, more than half of IWE without IBS also had abnormal findings for these parameters.…”
Section: Discussionmentioning
confidence: 61%
“…10 The association between the two conditions has been investigated by three recent systematic reviews, all of which found evidence of two-to three-fold risk of IBS in IWE compared to those without endometriosis. 11,12,30 Nabi et al 30 who analysed 17 studies (n = 96,974), reported a pooled prevalence of IBS in women with endometriosis of 23.4%. Saidi et al 12 identified a gap in adjusting for factors that may have affected gastrointestinal symptoms (e.g., phases of the menstrual cycle and psychological aspects).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this relationship remained significant after adjusting for other exposure covariates in the multivariate regression analysis. As a common gynecological disorder with high prevalence, EM seriously affects people of childbearing age [18]. While inflammation is a key physiological and pathological feature of EM, the altered inflammatory microenvironment in endometriotic tissue may lead to the persistence of chronic pain [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional therapies include danazol, progesterone, NSAIDs, etc. [ 8 , 9 , 10 , 11 ]. The drugs mentioned aim to lower estrogen levels, raise progesterone levels, or suppress inflammation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%